Effect of platelet-rich plasma on the rate of orthodontic tooth movement:: A split-mouth randomized trial - El-Timamy, Ahmed (Angle Orthod, 2020)
OBJECTIVE: To investigate the effect of local injection of platelet-rich plasma (PRP) on the rate of orthodontic tooth movement. MATERIALS AND METHODS: Sixteen female patients were randomly allocated in a split-mouth study design to receive PRP injections with CaCl(2) activating solution on one side (intervention side) while the other side received CaCl(2) injection only (control side). Canine retraction was performed on 0.017 × 0.025-inch stainless steel archwire applying 1.5 N retraction force. PRP and CaCl(2) injections were done at 0, 3, and 6 weeks. The duration of the study was 4 months. Data were collected from digitized models. Assessment of pain accompanying the procedure was done using a visual analogue scale. RESULTS: The rate of canine retraction was faster on the intervention side in the first 2 months, with a statistically significant difference in the first month (P = .049). On the other hand, the rate was statistically significantly slower on the intervention side in the third month following cessation of PRP injections (P = .02). Pain increased following injections on both sides. CONCLUSIONS: PRP showed a positive potential to accelerate the rate of tooth movement when injected in the first 2 months. Repeated injections of PRP to maintain a steady rate of accelerated tooth movement warrant further investigation.